Clinical Implications of Minimal Residual Disease Detection in Infants With KMT2A-Rearranged Acute Lymphoblastic Leukemia Treated on the Interfant-06 Protocol. Issue 6 (20th February 2021) - Stutterheim, Janine; van der Sluis, Inge M.; de Lorenzo, Paola; Alten, Julia; Ancliffe, Philip; Attarbaschi, Andishe; Brethon, Benoit; Biondi, Andrea; Campbell, Myriam; Cazzaniga, Giovanni; Escherich, Gabriele; Ferster, Alina; et al.
Abstract : PURPOSE: Infant acute lymphoblastic leukemia (ALL) is characterized by a high incidence of KMT2A gene rearrangements and poor outcome. We evaluated the value of minimal residual disease (MRD) in infants with KMT2A -rearranged ALL treated within the Interfant-06 protocol, which compared lymphoid-style consolidation (protocol IB) versus myeloid-style consolidation (araC, daunorubicin, etoposide/mitoxantrone, araC, etoposide). MATERIALS AND METHODS: MRD was measured in 249 infants by DNA-based polymerase chain reaction of rearranged KMT2A, immunoglobulin, and/or T-cell receptor genes, at the end of induction (EOI) and end of consolidation (EOC). MRD results were classified as negative, intermediate (< 5 × 10 −4 ), and high (≥ 5 × 10 −4 ). RESULTS: EOI MRD levels predicted outcome with 6-year disease-free survival (DFS) of 60.2% (95% CI, 43.2 to 73.6), 45.0% (95% CI, 28.3 to 53.1), and 33.8% (95% CI, 23.8 to 44.1) for infants with negative, intermediate, and high EOI MRD levels, respectively ( P = .0039). EOC MRD levels were also predictive of outcome, with 6-year DFS of 68.2% (95% CI, 55.2 to 78.1), 40.1% (95% CI, 28.1 to 51.9), and 11.9% (95% CI, 2.6 to 29.1) for infants with negative, intermediate, and high EOC MRD levels, respectively ( P < .0001). Analysis of EOI MRD according to the type of consolidation treatment showed that infants treated with lymphoid-style consolidation had 6-year DFS of 78.2% (95% CI, 51.4 to 91.3), 47.2% (95% CI, 33.0 to 60.1), and 23.2% (95% CI, 12.1 to 36.4) for negative, intermediate, and high MRD levels, respectively ( P < .0001), while for myeloid-style–treated patients the corresponding figures were 45.0% (95% CI, 23.9 to 64.1), 41.3% (95% CI, 23.2 to 58.5), and 45.9% (95% CI, 29.4 to 60.9). CONCLUSION: This study provides support for the idea that induction therapy selects patients for subsequent therapy; infants with high EOI MRD may benefit from AML-like consolidation (DFS 45.9% v 23.2%), whereas patients with low EOI MRD may benefit from ALL-like consolidation (DFS 78.2% v 45.0%). Patients with positive EOC MRD had dismal outcomes. These findings will be used for treatment interventions in the next Interfant protocol.